2009
DOI: 10.1093/bja/aen387
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor-evoked hippocampal norepinephrine release is highly sensitive to inhibition by isoflurane

Abstract: Background. Inhaled anaesthetics (IAs) produce multiple dose-dependent behavioural effects including amnesia, hypnosis, and immobility in response to painful stimuli that are mediated by distinct anatomical, cellular, and molecular mechanisms. Amnesia is produced at lower anaesthetic concentrations compared with hypnosis or immobility. Nicotinic acetylcholine receptors (nAChRs) modulate hippocampal neural network correlates of memory and are highly sensitive to IAs. Activation of hippocampal nAChRs stimulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…The classical α7 nAChR antagonist, MLA, also potently (IC 50 = 275 nM) inhibited nicotine-evoked [ 3 H]NE, but maximal inhibition was incomplete (I max = 72%). The current results are consistent with a recent in vitro study which found that MLA (10 μM) inhibits nicotine (100 μM)-evoked [ 3 H]NE from rat hippocampal synaptosomes [51], and with in vivo microdialysis studies showing that MLA (microdialysis probe concentrations of 0.4 – 32 nM) inhibits nicotine-evoked NE release from rat hippocampus [52]. α7* nAChRs are thought to mediate NE release from hippocampus through an indirect mechanism, i.e., α7*-mediated stimulation of glutamate release, which in turn promotes NE release [53].…”
Section: Discussionsupporting
confidence: 93%
“…The classical α7 nAChR antagonist, MLA, also potently (IC 50 = 275 nM) inhibited nicotine-evoked [ 3 H]NE, but maximal inhibition was incomplete (I max = 72%). The current results are consistent with a recent in vitro study which found that MLA (10 μM) inhibits nicotine (100 μM)-evoked [ 3 H]NE from rat hippocampal synaptosomes [51], and with in vivo microdialysis studies showing that MLA (microdialysis probe concentrations of 0.4 – 32 nM) inhibits nicotine-evoked NE release from rat hippocampus [52]. α7* nAChRs are thought to mediate NE release from hippocampus through an indirect mechanism, i.e., α7*-mediated stimulation of glutamate release, which in turn promotes NE release [53].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, nicotine may affect inhibition by interacting with dopaminergic systems that regulate reward and motivational processes (Viggiano et al, 2002). Similarly, nicotine has also been shown to stimulate the release of norepinephrine (Sterley et al, 2014; Westphalen et al, 2009; Zhao et al, 2007), which among other functions, modulates attention by regulating activity of prefrontal cortical neurons (Newman et al, 2008; McGaughy et al, 2008). We have previously shown that negative occasion setting is dependent on the prefrontal cortex (MacLeod & Bucci, 2010) and thus nicotine may act to enhance negative occasion setting by altering attentional functions mediated by prefrontal norepinephrine levels.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is critically involved in learning and memory processes (Lisman and Grace, 2005), and has been proposed as an important locus for anesthetic action (Pearce et al, 1989; Westphalen et al, 2009). Modulation of specific glutamatergic and dopaminergic signaling pathways supports anesthetic effects on transmitter release in mouse striatum in vivo (Snyder et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that regional differences in anesthetic sensitivity also exist for other transmitters based on their distinct presynaptic regulatory mechanisms (Snyder et al, 2007; Verhage et al, 1992). This is exemplified by the more potent inhibition by isoflurane of acetylcholine-evoked norepinephrine release from hippocampal nerve terminals mediated by presynaptic nicotinic acetylcholine receptors (Westphalen et al, 2009), and by the lesser anesthetic sensitivity of neuropeptide transmitter release from large dense core vesicles (Pashkov and Hemmings, 2002). …”
Section: Discussionmentioning
confidence: 99%